Peningkatan Kompetensi Guru dalam Menyusun Silabus dan RPP melalui Supervisi Akademik di MI Muhammadiyah Grubug Nanggulan Kulon Progo - Juminta (Jurnal Pendidikan Madrasah, 2020)
This research aims to improve the competence of MI teacher Muhammadiyah Grubug in compiling syllabus and RPP. This research is an action study through academic supervision activities. The subject of the study was MI teacher Muhammadiyah Grubug. The research was conducted in two cycles covering observation and discussion activities. The results showed that in cycle I the improvement in teacher competency reached 22% and increased to 67% in cycle II. Academic supervision activities can significantly improve the ability of MI Muhammadiyah Grubug teachers in compiling syllabuses and RPP.